2005
DOI: 10.1111/j.1365-3083.2005.01664.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Productive Antigen‐Processing Activity for MHC class II Presentation in Macrophages

Abstract: We demonstrated that an epitope from the recombinant protective antigen (rPA) of Bacillus anthracis was presented by mature major histocompatibility complex class II (MHC-II) molecules, whereas an epitope from the recombinant virulent (rV) antigen of Yersinia pestis was presented by newly synthesized MHC-II. We addressed which endosomal compartments were involved in the antigen processing of each epitope. Bone-marrow-derived macrophages were subjected to subcellular fractionation; fractions were analysed for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…In fact, we have found that the kinetics of cell surface pMHC-II arrival on CD63 ϩ antigen processing compartments is significantly delayed relative to that of cell surface MHC-II-Ii complexes. 4 We have also found that internalized MHC-II from the cell surface can traffic back to multivesicular bodies and be secreted on exosomes from B cells (47), demonstrated that the endocytosis pathway identified here leads to MHC-II delivery to multivesicular antigen processing compartments. Given the large number of pMHC-II on the cell surface at any given time, clathrin-and dynamin-independent endocytosis of Ii-free pMHC-II to both early endosomal and lysosomelike antigen processing compartments could be a major source of MHC-II for peptide loading (as discussed below).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In fact, we have found that the kinetics of cell surface pMHC-II arrival on CD63 ϩ antigen processing compartments is significantly delayed relative to that of cell surface MHC-II-Ii complexes. 4 We have also found that internalized MHC-II from the cell surface can traffic back to multivesicular bodies and be secreted on exosomes from B cells (47), demonstrated that the endocytosis pathway identified here leads to MHC-II delivery to multivesicular antigen processing compartments. Given the large number of pMHC-II on the cell surface at any given time, clathrin-and dynamin-independent endocytosis of Ii-free pMHC-II to both early endosomal and lysosomelike antigen processing compartments could be a major source of MHC-II for peptide loading (as discussed below).…”
Section: Discussionmentioning
confidence: 90%
“…In agreement with this, we find that mutation of the target lysine of MHC-II ubiquitination has no effect on the kinetics of pMHC-II endocytosis in HeLa-CIITA cells. 4 S22N mutant (panel B). The distribution of each endosomal protein (green) and internalized pMHC-II (red) was analyzed by confocal microscopy as described above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The STAT-1-signaling route is connected to the induction of MHC II expression and transport to antigen-loading compartments (MIIC) (23). MIIC vesicles contain MHC II molecules loaded with peptides (26), and SDS-stable ␣␤ MHC II dimers provide a valid measurement of peptide-loaded MHC II molecules (27)(28)(29). We found that the phagosomes (P-IFN, P-IL-6, and P-NT lanes in Fig.…”
Section: Ifn-␥ and Il-6 Trigger Similar Listericidal Mechanisms In Mømentioning
confidence: 92%
“…We based our hypothesis on two observations: (i) different MIIC and phagocytic vesicles contain LAMP-1 and LIMP-2 as characteristic markers (11,17,19,20,(23)(24)(25)(26), and (ii) both proteins appear as key regulators of late trafficking events (19,(27)(28)(29). Therefore, they were good candidates for the molecules that connect the late trafficking processes with innate immunity to LM.…”
mentioning
confidence: 99%